PELAT PANEL REACTIVE POWDER CONCRETE SEBAGAI LANDASAN PERALATAN PERMAINAN ANAK - Kushartomo, Widodo; Andryanto, Jonathan; Aaron, Jonathan; Carolina, Octavia (Jurnal Serina Abdimas, 2023)
Reactive Powder Concrete (RPC) is a material that has excellent mechanical properties. From various studies that have been carried out, it shows excellent mechanical properties, namely the compressive strength can reach 200 MPa and fracture toughness can reach above 30 MPa. The enormous compressive and flexural strength allows RPC to be used in various building structural elements such as beams, columns or plates or other uses. RPC is able to answer the challenges of the building construction industry to create very tall buildings and very long spans. With enormous power, the RPC can be designed in a slim way so that it can reduce its own burden very significantly. The research team of the Undergraduate Civil Engineering Study Program, Tarumanagara University, has developed RPC technology and is able to produce compressive strengths above 150 MPa and fracture toughness reaching above 30 MPa. The research team is also developing RPC applications in various applications such as retrofitting, bamboo joints and so on. The PkM team for the Civil Engineering Undergraduate Study Program, Tarumanagara University partnered with residents of RW 07, Banjar Wijaya Housing, Cipete Village, Pinang District, Tangerang City. Partners have problems placing children's play equipment in the form of swings, slides and monkey bars on a thin but strong platform. Based on the residents' difficulties in making a thin but strong foundation, the PkM team of the Department of Civil Engineering at Tarumanagara University used RPC technology to make panel plates as the basis for thin and strong children's play equipment. Reactive Powder Concrete (RPC) merupakan material yang mempunyai sifat mekanik sangat baik. Dari berbagai penelitian yang telah dilakukan menunjukkan sifat mekanis yang sangat baik yaitu kekuatan tekan mampu mencapai 200 MPa dan fracture toughness mampu mencapai diatas 30 MPa. Kekuatan tekan dan lentur sangat besar tersebut memungkinkan RPC digunakan dalam berbagai elemen struktur bangunan seperti sebagai balok, kolom ataupun pelat atau penggunaan lainnya. RPC mampu menjawab tantangan industri konstruksi bangunan untuk membuat bangunan yang sangat tinggi dan bentang yang sangat Panjang. Dengan kekuatan sangat besar RPC dapat didesain dengan ramping sehingga mampu mengurangi bebannya sendiri dengan sangat signifikan. Tim peneliti Program Studi Sarjana Teknik Sipil Universitas Tarumanagara, telah mengembangkan teknologi RPC dan mampu menghasilkan kekuatan tekan di atas 150 MPa dan fracture toughness mencapai di atas 30 MPa. Tim peneliti juga mengembangkan aplikasi RPC pada berbagai penggunaan seperti retrofit, sambungan bambu dan sebagainya. Tim PkM Program Studi Sarjana Teknik Sipil Universitas Tarumanagara bermitra dengan warga RW 07 Perumahan Banjar Wijaya Kelurahan Cipete Kecamatan Pinang Kota Tangerang. Mitra mengalami kendala menempatkan peralatan permainan anak berupa ayunan, seluncuran dan monkey bar pada landasan yang tipis namun kuat. Berdasarkan kesulitan warga untuk membuat landasan yang tipis namun kuat, tim PkM Jurusan Teknik Sipil Universitas Tarumanagara menggunakan teknologi RPC untuk membuat plat panel sebagai landasan peralatan permainan anak yang tipis dan kuat.